Strategi Pemasaran Untuk Meningkatkan Penjualan Umkm Tutut Pak Kumis Di Kabupaten Cianjur - Rachima Az Zahra; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to observe marketing strategies to increase sales in Micro, Small, and Medium Enterprises of Cianjur Regency in Tutut Pak Kumis MSMEs. This research method uses qualitative data analysis techniques as a process of searching and organizing data, such as interviews, field notes and other materials during the research period (data collection), after data collection using the core interview records and standards developed. The results of the research were obtained that Tutut Pak Kumis MSMEs still have not expanded their marketing strategy using online media and only carry out business activities at home, sales to local residents as well as CarFreeDay and consumers who are regular customers. However, MSMEs plan to use social media in the future to use social media to reach a wider range of marketing.